Optimisation of compositions and heat treatments of PT-based superalloys - Shongwe, Mxolisi Brendon (My University, 2009)
ABSTRACT This study investigated the optimisation of compositions and heat treatment of Pt-based Pt- Al-Cr-Ru superalloys. Initially, six alloys of different compositions were selected using an optimum composition from previous research as a starting point. These alloys were analysed in both the as-cast and heat treated conditions. The heat treatment comprised two stages, first at 1500°C for 18 hours and quenched in water, followed by 1100°C for 120 hours and then air cooled. Microstructural characterisation was carried out in an HR FEI Nova NanoSEM in BSE mode, also using EDX, and XRD. The as-cast alloys had (Pt) dendrites with a eutectic/eutectoid of (Pt) + ~Pt3Al, with tetragonal ~Pt3Al precipitated in the dendrites. All heat treated alloys had precipitates of tetragonal ~Pt3Al in a (Pt) matrix. The volume fraction of the precipitates varied, and the maximum proportion was 30%. To increase the volume fraction, more samples were made with 11 at.% Al. All of the 78 at.% Pt alloys had more ~Pt3Al precipitates than the 80 at.% Pt alloys, and the Pt80:Al11:Ru5:Cr4 alloy had no discernable precipitates. The microstructure was similar to the first batch of samples and Pt78:Al11:Ru5:Cr6 had the highest precipitate volume fraction. The hardness of the alloys was also studied in both conditions. Cracking and slip modes around the hardness indentations were studied to evaluate the toughness. In both conditions, most of the alloys had high hardnesses and exhibited wavy slip, with no cracking from the indentation corners. Pt78:Al11:Ru5:Cr6 was the promising alloy because it had the best microstructure (highest proportion of precipitates), a high Al content for oxidation resistance and a reasonable low Pt content for both reduction in price and density.